Validasi Kelayakan E-Modul Pajak Penghasilan Berbasis Canva dalam Pembelajaran Perpajakan di Sekolah Menengah Kejuruan - Anggraini, Yovita Dwi; Jaenudin, Riswan; Safitri , Erna Retna (Jayapangus Press, 2025)
This study aims to determine the feasibility of a Canva-based Income Tax e-module as a learning medium in Vocational High Schools (SMK). It is part of a development research project using a descriptive quantitative approach, with expert validation as the main method. Three validators were involved in the validation process, consisting of a subject matter expert, a language expert, and a media expert. The instrument used was an assessment sheet employing a Likert scale to evaluate the feasibility of the e-module in terms of content accuracy, language use, and media design. The validation results showed that the e-module received an average score of 88% from the content expert, 94% from the language expert, and 89% from the media expert, all of which fall under the